Evaluasi Program Pendidikan Karakter dalam Meningkatkan Kualitas di Pondok Pesantren Al-Husna Marindal - Inom Nasution; Nadia Anggraini; Clara Tri Putri; Elvi i Azizah; Sari Bulan Hasibuan; Yunita Aisyah (JURNAL EDUKASI NONFORMAL, 2023)
the implementation of character education aims to improve the quality of education which leads to the process of achieving the formation of the character of students as a whole, integrated and balanced, according to standards Graduate of. The success of character education can be measured through a thorough evaluation consisting of: 1) Evaluation of the context which includes the basis of the policy, the perception of the needs and objectives of the character education program; 2) input evaluation which includes planning, strategy, organizational structure design, Implementation procedures and availability of character education program resources; 3) Process evaluation which includes processes that include coordination, implementation and supervision of the implementation of character education programs; 4) Product evaluation which includes the achievement and impact of the character education program. Evaluation of character education programs is carried out to provide reinforcement, Improvement and measure the success of the implementation of character education programs carried out by education providers.